INTERACTION OF SOCIAL PROCESSES IN WORD FORMATION BY A COMPOSITIONAL WAY - R.Opayeva (Galaxy International Interdisciplinary Research Journal, 2022)
It is formed making compound words in the process of word formation which is one of the aspects of world linguistics that clarifies the broad internal possibilities of any language, comprehensive study of words belonging to such a group at the grammatical level of language, as well as experiments in the use of research results. Comparing the methods of compound words with the sister Turkic languages, identifying the objects of formation of compound words, studying the structure and types of compound words in historical and modern aspects are issues on the agenda. Historical-linguistic study of compound words has a great importance in special study of the Karakalpak language, in particular, studying the system of its word formation specifically.